Barile's clinical toxicology : principles and mechanisms - Barile, Frank A. (Boca Raton, FL : CRC Press, 2019)
Examines the complex interactions associated with clinical toxicological events as a result of therapeutic drug administration or chemical exposure. Special emphasis is placed on signs and symptoms of diseases and pathology caused by toxins and clinical drugs. Includes the source, pharmacological and toxicological mechanism of action, detection and identification in body fluids, and treatment of exposure. An overview of protocols for managing various toxic ingestions, and the antidotes and treatments associated with their pathology, are discussed. In addition, effect of toxins on a limited number of body systems and drug-induced adverse drug reactions are also covered.
OCLC-licensed vendor bibliographic record.
Keywords: Clinical toxicology; Toxicology -- Standards; Toxicity testing; Clinical pharmacology -- Standards; MEDICAL / Pharmacology; MEDICAL / Neuroscience